Analisis Wacana Terhadap Berita Radio Republik Indonesia Kupang pada Acara Warta Berita Daerah Pagi - Nafie, Juan Ardiles (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
Abstract:Title of this appointed by the background thinking tends to assume the news radio is the boring, stiff and monotonous and thus author shall select said that the news visible life easier understood listeners and the said right of news. Thus the formula problem in this is how the language used in writing of news Radio Republic Indonesia Kupang on a news areas morning. This watchfulness aims to detect radio language that used in Kupang Republic of Indonesia radionews writing, in region news report programme morning.this watchfulness uses to approach qualitative with a view to get description about language in Kupang Republic of Indonesia Radionews writing in region news report programme morning. data collecting technique that used recording, interview, and documentation Research results that news news still use the word wasteful or not use the sentence brief congested and said there are still doble said a word, there is a foreign language not included meaning, there are error of writing the name of informant, principle of usage punctuation frequently used in writing the news radio not wear Keywords: News, Language, Radio